(3GdLhGgQ GdNeSs - (3GHf NWjQ GdOjf , eMeO Hf NWjQ Hf HGjRjO GdYWGQ, CHh GdeDjO,J (B970 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdCMO GdUeO GdaQO GdPi de jdO hde jhdO hde jcf dg cahkG CMO MeOkG HdG HOGjI s
(3BNQgG (B:s
(3hGdefWhb ai cd dSGf hEf de jJbGd hgh GdcHjQ GdeJYGd gPG GdcJGH GdeSei HLhGgQ NeSg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B282s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMQha h GdChaGbs